A short guide to understanding behavioural difficulties. Issue 8 (28th June 2013) - Spender, Quentin
Abstract : An approach to behaviour problems presenting in a paediatric context is described. This model aims to generate a form of understanding that is not only accessible but can also generate management strategies.